Uncovering The Determinants Of Sustainability Practices: Perceptive Of Small Scale Dairy Farmers - Nalini, Arumugam; Zainab, Mohd Karim (2018)
Aim/Purpose This research will explore the factors that determine the level of adoption and participation in sustainability practices among the local dairy farmers in Malaysia.